(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Indonesia’s e-commerce growth has increased by 17% in the last ten years. One of the most popular e-commerce businesses in Indonesia is online food delivery services. Promotion is one of the reasons that makes online food delivery service users increase every year. This research aims in alayzing the effects of e-service quality (e-servqual), food quality, and sales promotion toward perceived value and customer satisfaction, as well as their impacts on customer loyalty. A questionnaire was distributed to 200 respondents who had used online food delivery services in DKI Jakarta. The Structural Equation Model (SEM) with the PLS-SEM was used to test the validity, reliability, and hypothesis. The results of this study indicate that customers satisfaction impacted customer loyalty, which is the benchmark for customers in using online food delivery services. Not only that, company’s services, quality, and promotion impact customer satisfaction.